Pengenalan Bisnis Berbasis Digital kepada Mahasiswa Prodi Hubungan Internasional FISIP Universitas Sulawesi Barat - Riady Ibnu Khaldun; Sriwiyata Ismail (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service activity titled "Introduction to Digital-Based Business for Students of the International Relations Study Program at the Faculty of Social and Political Sciences, University of West Sulawesi" aligns with one of the subjects in the Digital Economy and Popular Culture course. This activity was conducted in the twelfth meeting in accordance with the Semester Learning Plan Document, which includes a field visit to a type of business that utilizes digital business concepts before preparing the final project. The goal of this activity is to enhance students' understanding and skills in leveraging digital technology for business, emphasizing its impact on the dynamics of international relations. Through the organization of interactive seminars, students were given an understanding of basic digital business concepts, online marketing strategies, e-commerce management, and the role of social media in business promotion. Additionally, this community service activity also introduced students, who were also participants, to the connections between digital business and international relations such as global trade, economic cooperation between countries, and digital diplomacy. The results of this activity showed an increase in students' knowledge and interest in digital business, including the development of innovative business ideas that are competitive in the digital era and able to adapt to the dynamics of the global market. Furthermore, this activity also provided benefits in the form of improving students' skills in digital business and understanding the impact of implementing digital business in international relations.